Development of a drip irrigation system for a coconut farm - Marasigan, Marvi V.; Murty, V.V.N.; Goto, Akira; Upasena, Selawa H.; Federal Republic of Germany (DAAD) under t he Bilateral Technical Assistance Program (Bangkok : Asian Institute of Technology, 1990)
This study is aimed to develop a design of drip irrigation system for coconut, determine its cost under local conditions and to develop an interactive computer program for the design of the system. The estimated crop water requirement of coconut in the experimental area in Philippines was equal to 4.0 mm/day. A depth of 65 mm/irrigation of water and an interval of irrigation of 17 days are necessary for the irrigation. Five drippers having a flowrate of 4 lph/dripper are recommended to a coconut tree. Designs of drip irrigation for the experimental site and for various farm sizes using local materials were prepared and corresponding cost estimates and analysis were made. For a hectare of coconut, an establishment cost of P68,860.00 ($3,130.00) and operating expenses of PB0.00 ($4.00)/irrigation are estimated considering the costs in the year 1990. Finally, an interactive computer model for designing drip system for coconut operating under different conditions is presented. The model is useful for designing systems of varying farm sizes and with intercrops of coffee and blackpepper.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Irrigation farming; Coconut